C-reactive protein and thyroid-stimulating hormone levels as risk factors for hypothyroidism in patients with subacute thyroiditis. Issue 8 (13th August 2021) - Tang, Chenjia; Dong, Yanting; Lu, Lusi; Zhang, Nan
Abstract : Objective: This study was designed to explore the relationships between the clinical characteristics and outcomes of patients with subacute thyroiditis (SAT). Design: This is a single-center retrospective study. Patients: Eighty-nine patients with SAT who were hospitalized in the Sir Run Run Shaw Hospital in Zhejiang, China, from October 2014 to September 2020 were included. Methods: The Mann–Whitney U -test, chi-square test, and Cox regression analysis were conducted to identify the relationships between clinical characteristics and outcomes. Receiver operating characteristic (ROC) analysis was performed to determine the optimal cutoff levels of C-reactive protein (CRP) and thyroid-stimulating hormone (TSH). Results: The hypothyroidism and recurrence rates were 15.7 and 16.9%, respectively. CRP (≥72.0 mg/L), TSH (<0.02 mIU/L), and free triiodothyronine (fT3) (≥4.10 pg/mL) were associated with hypothyroidism. The cutoff level was 97.80 mg/L for CRP (area under the curve (AUC), 0.717, P = 0.014; sensitivity, 57.1%; specificity, 84.0%) and 0.10 mIU/L for TSH (AUC, 0.752, P = 0.004; sensitivity, 100%; specificity, 46.0%) by ROC curve analysis for hypothyroidism. The factors under study were not associated with recurrence. Conclusion: CRP and TSH were risk factors for hypothyroidism in SAT. Thyroid functions should be monitored closely for the early detection of hypothyroidism, especially in patients with CRP levels of more than 97.80 mg/L and TSH levels of less than 0.10 mIU/L.